Electronic structure regulation of noble metal-free materials toward alkaline oxygen electrocatalysis - Wang, Xia; Yu, Minghao; Feng, Xinliang (eScience (Beijing), 2023)
Developing highly efficient, inexpensive catalysts for oxygen electrocatalysis in alkaline electrolytes (i.e., the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER)) is essential for constructing advanced energy conversion techniques (such as electrolyzers, fuel cells, and metal–air batteries). Recent achievements in efficient noble metal-free ORR and OER catalysts make the replacement of conventional noble metal counterparts a realistic possibility. In particular, various electronic structure regulation strategies have been employed to endow these oxygen catalysts with attractive physicochemical properties and strong synergistic effects, providing significant fundamental understanding to advance in this direction. This review article summarizes recently developed electronic structure regulation strategies for three types of noble metal-free oxygen catalysts: transition metal compounds, single-atom catalysts, and metal-free catalysts. We begin by briefly presenting the basic ORR and OER reaction mechanisms, following this with an analysis of the fundamental relationship between electronic structure and intrinsic electrocatalytic activity for the three categories of catalysts. Subsequently, recent advances in electronic structure regulation strategies for noble metal-free ORR and OER catalysts are systematically discussed. We conclude by summarizing the remaining challenges and presenting our outlook on the future for designing and synthesizing noble metal-free oxygen electrocatalysts.